Spherically symmetric random permutations. Issue 2 (7th March 2019) - Gnedin, Alexander; Gorin, Vadim
Abstract : We consider random permutations which are spherically symmetric with respect to a metric on the symmetric group S n and are consistent as n varies. The extreme infinitely spherically symmetric permutation‐valued processes are identified for the Hamming, Kendall‐tau and Cayley metrics. The proofs in all three cases are based on a unified approach through stochastic monotonicity.